What the Water Sector Can Learn From Recent Weather Disasters. Issue 9 (1st September 2013) - Spence, Shannon; Moyer, Jack
Abstract : The years 2011 and 2012 were unprecedented in the weather extremes and disasters they presented. Those weather patterns and incidents have provided strong lessons and reminders to the water sector and others about key preparedness actions that should be taken. These recent weather disasters provide an opportunity to review what the water sector can learn from them and underscores the need for disaster preparedness.